Modeling the effects of extreme precipitation on groundwater resource components of Dagu aquifer in China - Pengpeng Zhou; Suna Li; Guangcai Wang; Xiaoxi Yu; Jiani Fu (Journal of Hydrology: Regional Studies)
Study Region: Dagu aquifer is a water resource area and situated in the northwest of Qingdao, China. Study Focus: Investigating effects of extreme precipitation on groundwater resource is vital for sustainability of water resource and ecosystem. However, effects of extreme precipitation characteristics on different groundwater resource components and response degrees of these components to extreme precipitation remain poorly understood. To address this, groundwater modeling and multi-scenario simulations were conducted. Correlation analysis and sensitivity coefficient were then used to reveal the effects of extreme precipitation on different groundwater resource components. New Hydrological Insights for the Region: Extreme precipitation characterized by high precipitation amount, great intensity, a large number of moderate/heavy rain days, and maximum 1-day or 5-day precipitation amount significantly increases infiltration recharge and groundwater storage. Extreme precipitation with extremely high precipitation amount, a large number of rainstorm days, and maximum 1-day precipitation amount takes certain positive effects on river leakage. Sensitivity results showed that groundwater storage has the most significant response to extreme precipitation with sensitivity coefficients of 4.96–6.28, and total groundwater recharge is also sensitive to the extreme precipitation with sensitivity coefficients of 0.84–1.01, while the response of total groundwater discharge is the weakest. These findings contribute to quantitative understandings of the relationship between extreme precipitation and groundwater resource components in single-layer unconfined aquifers, and provide useful insights for sustainable groundwater management.